Green Public Financial Management in Indonesian Public Sector Accounting: A Literature Review - Yosep Fristamara; Kadek Supri Budiadnyana; Made Aristia Prayudi (KRISNA: Kumpulan Riset Akuntansi, 2026)
This literature review examines the role of public sector accounting in achieving Green Public Financial Management (GPFM) in Indonesia through a synthesis of six peer-reviewed articles (2004-2025). Using the PT Timah case in Raja Ampat as an illustrative example, the study demonstrates that traditional public financial management systems systematically undervalue natural capital and environmental costs. The findings reveal a strong positive correlation between accounting quality and sustainability outcomes; however, implementation is constrained by limited institutional capacity, regulatory gaps, and short-term economic priorities. Indonesia's digital infrastructure, decentralized governance system, and international commitments create opportunities for innovative GPFM approaches. The transformation of public sector accounting from a compliance mechanism to a strategic sustainability instrument requires a comprehensive regulatory framework and inter-ministerial coordination. GPFM implementation represents both a critical imperative and an opportunity to achieve sustainable development while contributing to global climate objectives.